WORK FROM ANYWHERE TERHADAP KEPUASAN KERJA DIMEDIASI OLEH SOFT DAN HARD COMPETENCY DI PT POS INDONESIA SIDOARJO - Nur Layli Fatikhatun Nissa; Sherly Amalia Fernanda; Wahyu Eko Pujianto (Journal of Applied Management Studies, 2023)
Work from anywhere has become a trend in today’s digital era, especially during the Covid- 19 pandemic which forced many employees to work from home. Although work from anywhere has brought benefits such as flexibility and convenience, it has also created several challenges, such as difficulties in maintaining work order and lack of social interaction with colleagues. The purpose of this study was to determine the effect of work from anywhere on job satusfaction and increase job satisfaction by prioritizing initiative and independence among employees to implement work effectiveness mediated by soft and hard competencies. The method used in this research is quantitative with an explanatory approach